Three new genera from South America and some taxonomic changes in Gyponini (Insecta: Hemiptera: Cicadellidae) - Gonçalves, Clayton C.; Domahovski, Alexandre C.; Mejdalani, Gabriel; Takiya, Daniela M. (European Journal of Taxonomy, 2021)
Three new South American leafhopper genera of the tribe Gyponini are proposed: Beltrana gen. nov. based on Beltrana reticulata gen. et sp. nov. from French Guiana, Fulana gen. nov. based on Fulana brasiliensis gen. et sp. nov. from Brazil, and Sicrana gen. nov. based on Sicrana plana gen. et sp. nov. from Brazil and Ecuador. Diagnoses, detailed descriptions, and illustrations are provided for each taxon, as well as comparisons with closely related genera. In addition, the following synonyms are proposed: Freytagana DeLong, 1975 as a junior synonym of Marganana DeLong, 1948 and F. gibsoni DeLong, 1975 as a junior synonym of M. (Marganana) mexicana DeLong & Freytag, 1963. Chilella DeLong & Freytag, 1967 is transferred from Gyponini to Selenomorphini Evans, 1974.